Ketercapaian Tugas-Tugas Perkembangan Remaja dan Pendidikan Seksual Pada Remaja - Fuaddillah Putra; Ramdani Ramdani (Jurnal Konseling dan Pendidikan, 2014)
Adolescence is a transitional period between childhood into adulthood, or period of a years, during which time they must meet some development tasks. Adolescent development tasks must be accomplished by a teenager. Fostering social relationships closer to same-sex and opposite sex friends is one of the nine developmental tasks that must be met by teenagers. The development task in achieving common understanding of the crisis affecting the values and morals that occurred in the community, such as the occurrence of free sex among teenagers. The occurrence of free sex for example form a misunderstanding of the meaning of fostering social connections among these teens, can be caused by a lack of sex education, information obtained by the teenagers, both from the family environment as well as from the environment outside the family (society and education in schools). Sex education is education which is given to individuals and discuss about reproductive health as well as things that can cause teens are no longer responsible for the reproductive organs. Fulfilling the development tasks that should be fulfilled by the teens must be accompanied by the guidance they can get from the people around them, thus fulfilling the development tasks can be in accordance with the values and norms that apply in an environment where they do the activity of life.